Using social media marketing to pro-tourism behaviours: the mediating role of destination attractiveness and attitude towards the positive impacts of tourism - Zyad M. Alzaydi; Mohamed H. Elsharnouby (Future Business Journal)
Abstract Social media has recently played a highly impactful role in communication. Specifically, these channels are vital and have a substantial influence on the attitudes, behavioural intentions, and actual behaviour of tourists. Previous research showed clearly that there is an increasing number of individuals who rely heavily on social media platforms for gathering information and gaining knowledge about various issues. The current research tries to show the impact of these platforms on citizens’—as individuals—attitudes and behaviours to support tourism activities. Specifically, the current study examines three research objectives: (1) The impact of social media marketing activities on pro-tourism behaviours. (2) The impact of social media marketing activities on both destination attractiveness and attitude towards the positive impacts of tourism. (3) The mediation role of destination attractiveness and attitude towards the positive impacts of tourism in the relationships between social media marketing activities and pro-tourism behaviours. We adapted the theory of uses and gratifications and the stimulus-organism-response framework in the current research, where social media marketing drives pro-tourism behaviours indirectly through both destination attractiveness and attitude towards the positive impacts of tourism. A survey of 200 Albaha residents was conducted. We have used AMOS to check the constructs’ validity and reliability and Hayes’s PROCESS macro to test the mediation. The findings show that (1) Social media marketing activities help in explaining why city citizens positively behave towards tourism activities in their city; (2) Sequentially both destination attractiveness and attitude towards the positive impacts of tourism partially mediate the relationships between social media marketing and pro-tourism behaviours. The current study contributes to the existing research through the elucidation of why residents behave to support tourism in their countries by using social media marketing activities. In addition, it adds a number of professional insights. For example, the admins of destination social media platforms should increase their efforts towards providing presence, conversation, interactivity, and sharing on these platforms.